Conflitos socioambientais na região de integração do Tocantins em torno da construção de um terminal portuário de uso privativo no município de Abaetetuba, Pará - Silva, Glauber Moraes (2023)
The present study analyzes the main socio-environmental issues surrounding the conflict between the riverside communities around Cargill's port and the company. Reflections and debates about the installation of the Cargill port in the region of the islands of the Municipality of Abaetetuba. The central problem focuses on the conflicts arising from socio-environmental issues between the interests of the riverside people of the area and the multinational company Cargill based in the United States around the construction of a Port Terminal for Private Use (TUP) on Xingu Island in the Municipality of Abaetetuba. In methodological terms, the work is organized having as a starting point the research locus and subsequent definition of the aspects of the investigation in relation to its approach, nature, objectives and procedures. The research has a mixed nature, that is, qualitative and quantitative. The work is divided into four sections: the first deals with the socioeconomic context of food production and distribution in the contemporary world; the second section deals with the production, circulation and disposal of grains in Brazil; the third discusses the road, waterway and railway infrastructure in Brazil and in the State of Pará; and finally, the fourth section addresses the Amazonian context of Cargill's ports: Santarém and Abaetetuba. Finally, in the final considerations, the author gives a general opinion on everything that was presented.